Cloning, expression, purification, crystallization and preliminary X‐ray diffraction analysis of AerF from Microcystis aeruginosa, a putative reductase participating in aeruginosin biosynthesis. Issue 4 (1st April 2015) - Ding, Ruyi; Xu, Cui; Chen, Xu; Bao, Mengyun; Qiu, Xiaoting
<x xml:space="preserve">Abstract</x> The 2‐carboxy‐6‐hydroxyoctahydroindole moiety is an essential residue for the antithrombotic activity of aeruginosins, which are a class of cyanobacteria‐derived bioactive linear tetrapeptides. The biosynthetic pathway of the 2‐carboxy‐6‐hydroxyoctahydroindole moiety has not yet been resolved. AerF was indicated to be involved in the biosynthesis of the 2‐carboxy‐6‐hydroxyoctahydroindole moiety. This study reports the cloning, expression, purification, crystallization and preliminary X‐ray diffraction analysis of AerF from Microcystis aeruginosa with a C‐terminal His6 tag. The crystal diffracted to a maximum resolution of 1.38 Å and belonged to the tetragonal space group P4322, with unit‐cell parameters a = b = 101.581, c = 116.094 Å. The calculated Matthews coefficient and solvent content of the crystal were 2.47 Å3 Da−1 and 50.32%, respectively. The initial model of the structure was obtained by the molecular‐replacement method and refinement of the structure is in progress.